2022
DOI: 10.3389/fmolb.2022.815320
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogens Eliminate Aging-Associated Synaptic Defects and Microglia-Mediated Neuroinflammation in Mice

Abstract: Neurodegeneration is a pathological condition in which nervous system or neuron losses its structure, function, or both leading to progressive neural degeneration. Growing evidence strongly suggests that reduction of plasmalogens (Pls), one of the key brain lipids, might be associated with multiple neurodegenerative diseases, including Alzheimer’s disease (AD). Plasmalogens are abundant members of ether-phospholipids. Approximately 1 in 5 phospholipids are plasmalogens in human tissue where they are particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 112 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…111 Previously, orally supplementing mice with an alkylglycerol mix also successfully rescued adipocyte morphology changes, while reducing diet-induced obesity. 112 During aging, a recent study by Gu et al (2022) indicates that systemically administering Pls to female mice for 2 months starting at 16 months of age increases hippocampal synaptic density and plasticity, as well as neurogenesis and cognitive performance, while decreasing hippocampal microglial reactivity (on a morphological level) and the concentration of inflammatory mediators (tumor necrosis factor α, interleukins 1β and 6). 109 In this study, purified Pls derived from the ascidian Halocynthia roretzi enriched in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), together with other omega-3 fatty acids, were used.…”
Section: Restoring Pls Levels As a Therapeutic Strategy In Chronic In...mentioning
confidence: 99%
See 2 more Smart Citations
“…111 Previously, orally supplementing mice with an alkylglycerol mix also successfully rescued adipocyte morphology changes, while reducing diet-induced obesity. 112 During aging, a recent study by Gu et al (2022) indicates that systemically administering Pls to female mice for 2 months starting at 16 months of age increases hippocampal synaptic density and plasticity, as well as neurogenesis and cognitive performance, while decreasing hippocampal microglial reactivity (on a morphological level) and the concentration of inflammatory mediators (tumor necrosis factor α, interleukins 1β and 6). 109 In this study, purified Pls derived from the ascidian Halocynthia roretzi enriched in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), together with other omega-3 fatty acids, were used.…”
Section: Restoring Pls Levels As a Therapeutic Strategy In Chronic In...mentioning
confidence: 99%
“…112 During aging, a recent study by Gu et al (2022) indicates that systemically administering Pls to female mice for 2 months starting at 16 months of age increases hippocampal synaptic density and plasticity, as well as neurogenesis and cognitive performance, while decreasing hippocampal microglial reactivity (on a morphological level) and the concentration of inflammatory mediators (tumor necrosis factor α, interleukins 1β and 6). 109 In this study, purified Pls derived from the ascidian Halocynthia roretzi enriched in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), together with other omega-3 fatty acids, were used. 109 Omega-3 fatty acids were importantly shown in a human clinical trial conducted in middle-age adults to slow down accelerated aging and reduce the depression risk by lowering overall inflammation and cortisol levels during stress, in addition to promoting immune repair mechanisms during recovery.…”
Section: Restoring Pls Levels As a Therapeutic Strategy In Chronic In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a simple method was developed to extract a large number of plasmalogens from animals ( Mawatari et al, 2007 ; Mawatari et al, 2009 ), which enabled research on plasmalogen treatment. In mice, plasmalogen administration not only suppressed inflammation-induced activation of microglia, amyloid formation, and neuronal cell death in the brain but also improved cognitive function ( Ifuku et al, 2012 ; Katafuchi et al, 2012 ; Hossain et al, 2013 ; Hossain et al, 2018 ; Gu et al, 2022 ; Hossain et al, 2022 ). A randomized controlled trial demonstrated that scallop-derived purified plasmalogens improved cognitive function in patients with mild AD or mild cognitive impairment ( Fujino et al, 2017 ; Fujino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmalogens are also involved in the regulation of protein kinase B (AKT) in Schwan cells, mouse embryonic fibroblasts, and neurons (da Silva et al, 2014;Malheiro et al, 2019;da Silva et al, 2021). In addition, supplementation of plasmalogens activates signaling pathways mediated by AKT, ERK, and brain-derived neurotrophic factors in cultured cells (Hossain et al, 2016;Che et al, 2020) and mice (Hossain et al, 2022), giving rise to enhanced learning and memory (Gu et al, 2022;Hossain et al, 2022), suggesting a potential function of plasmalogens in the regulation of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%